Answer: $2.40
Step-by-step explanation:
$60.00 x .04 = $2.40
Answer:
$8016.00
Step-by-step explanation:
I = 6000 × 0.042 × 8 = 2016
I = $ 2,016.00
$2,016.00 + $6,000.00 = 8,016.00
Answer:
Step-by-step explanation:
I think you have the question incomplete, and that this is the complete question
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
To do this, we can start my mirroring the equation.
x² + y² = (x + y)² - 2xy,
This helps us break down the power from 4 to 2, so that we have
(sin²a)² + (cos²a)² = (sin²a + cos²a) ² - 2(sin²a) (cos²a)
Recall from identity that
Sin²Φ + cos²Φ = 1, so therefore
(sin²a)² + (cos²a)² = 1² - 2(sin²a) (cos²a)
On expanding the power and the brackets, we find that we have the equation proved.
sin^4a + cos^4a = 1 - 2sin^2a.cos^2a
The answer to number 18 is - 0.25 or 1/4
If you need help with the other ones ask.
<em>Hope this will help :)</em>
Answer:
y=x no
y=12x yes
y=1.6x yes
y=3/(4x) no
y=2x+1 no
y=3+x no
Step-by-step explanation: